An efficient treatment of ultra-heavy asphaltic crude oil using electron beam technology. (15th August 2015) - Alfi, Masoud; Barrufet, Maria A.; Moreira, Rosana G.; Da Silva, Paulo F.; Mullins, Oliver C.
Highlights: Electron beam improves the viscosity reduction process during heavy oil upgrading. Different analytical techniques used to analyze physical and chemical changes. Irradiation provides an efficient energy transfer means to large hydrocarbons. High aromatic content alters the reaction mechanism of radiation thermal cracking. Electron irradiated samples exhibit a stable viscosity over time. Abstract: Electron beam technology, as a promising energy-efficient process, is used as a new treatment for ultra-heavy asphaltic petroleum fluids. Over the past few decades, heavy oil resources have been recognized to be among the most abundant sources of energy. However, extraction, transportation, and processing problems of these fluids still remain to be a challenge in the petroleum industry. The contribution of these hydrocarbon resources to the energy market has been impacted by the fact that the conventional upgrading and visbreaking methods demand a considerable energy investment. In this paper, we coupled electron beam irradiation with conventional thermal processing methods to find an energy-efficient way of improving unfavorable properties of heavy asphaltic hydrocarbons. Electron irradiation was observed to improve the viscosity reduction process by a factor of 30% compared to thermal treatment. Energy transfer process becomes more efficient in radiation-induced reactions, which results in an intensified cracking process. The role of complex asphaltene structures on radiation thermal cracking was investigated by using hydrocarbons with high and low asphaltene content. Our results showed that in samples with high asphaltene content, electron radiation impacts the reaction mechanism of the thermal cracking process. In fact, high energy electrons interact with aromatic structures of asphaltene molecules, resulting in products with a different hydrocarbon component distribution and time-stability properties, as opposed to the simple thermal cracking case. On the other hand, experiments showed thermal and radiation thermal cracking processes follow a similar reaction mechanism for hydrocarbons of low asphaltene content.